2006
DOI: 10.1196/annals.1371.019
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and Breast Cancer

Abstract: A local collaborative process was launched in Windsor, Ontario, Canada to explore the role of occupation as a risk factor for cancer. An initial hypothesis-generating study found an increased risk for breast cancer among women aged 55 years or younger who had ever worked in farming. On the basis of this result, a 2-year case-control study was undertaken to evaluate the lifetime occupational histories of women with breast cancer. The results indicate that women with breast cancer were nearly three times more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Two exploratory breast cancer case–control studies were undertaken by a multidisciplinary team of occupational and environmental researchers but had limited statistical power and exposure assessment. The first was a hypothesis-generating multi-cancer case control study [26]; the second study focussed exclusively on breast cancer [27]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two exploratory breast cancer case–control studies were undertaken by a multidisciplinary team of occupational and environmental researchers but had limited statistical power and exposure assessment. The first was a hypothesis-generating multi-cancer case control study [26]; the second study focussed exclusively on breast cancer [27]. …”
Section: Introductionmentioning
confidence: 99%
“…The prior hypotheses of the current breast cancer study were based on: a) previous work on the environmental causes of breast cancer, b) current theories of carcinogenesis and endocrine effects, and c) findings of a previous breast cancer study that observed: increased risks among women with an occupational history of farming (OR = 2.8; 95% CI, 1.6 - 4.8) and among those who subsequently worked in auto-related manufacturing (OR = 4.0; 95% CI, 1.7 - 9.9), or in health care (OR = 2.3; (95% CI, 1.1 - 4.6) [27]. In the same geographic area of Ontario, the present study includes: a much larger sample from a later and distinct time period; a more detailed classification of potential exposures; and a more extensive compilation of non-occupational risk factor information.…”
Section: Introductionmentioning
confidence: 99%
“…The risk for farm injury increased with level of stress (Simpson et al, 2004). Research has demonstrated a possible association between breast cancer and farming; women with breast cancer were nearly three times more likely to have worked in agriculture when compared to the controls (OR 2.8, 95% CI: 1.6-4.8) (Brophy et al, 2002(Brophy et al, , 2006. Similarly, studies have identified links between pesticide exposure and spontaneous abortion (Arbuckle et al, 1999a;Curtis et al, 1999;Kristensen, 1999).…”
mentioning
confidence: 97%
“…In a large cohort of female textile workers in China, increased risk of ovarian cancer was associated with work in textile finishing and exposure to silica dust. 151 Increased risk of ovarian cancer has been observed among women employed as chemists, engineers, or in laboratory occupations, 46 teachers, 61 cosmetologists, 20À22 dry cleaners, 33 nurses and radiologic technologists, 48,61,63,177 office and clerical workers. 61,292À293 Ovarian cancer has also been elevated in printing industries, 33,139,145 the semi-conductor industry, 112 women exposed to pesticides, 178,180,182 and in the aerospace industry in women exposed to trichloroethylene.…”
Section: Breastmentioning
confidence: 98%